Proceedings of the 2010 ICSE Workshop on Emerging Trends in Software Metrics 2010
DOI: 10.1145/1809223.1809231
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of coupling metrics on aspect-oriented programs

Abstract: Coupling metrics received increased recognition by objectoriented (OO) software developers when they were found to be indicators of important quality attributes, such as faultproneness. However, there is no consensus on which coupling metrics are effective quality indicators for emerging development paradigms, such as Aspect-Oriented Programming (AOP). AOP aims to improve software quality by providing significantly different decomposition mechanisms, such as pointcut, advice and intertype declarations. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Following recent studies [23,27], we target four releases of each system in our evaluation. These releases are iBATIS 01, 01.3, 01.5 and 02 3 , HealthWatcher 01, 04, 07 and 10 and MobileMedia 01, 02, 03 and 06.…”
Section: B the Target Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following recent studies [23,27], we target four releases of each system in our evaluation. These releases are iBATIS 01, 01.3, 01.5 and 02 3 , HealthWatcher 01, 04, 07 and 10 and MobileMedia 01, 02, 03 and 06.…”
Section: B the Target Systemsmentioning
confidence: 99%
“…Our previous work [23] compared the fault prediction ability of existing AOP metrics [11] with a novel, combined metric that takes into account the several coupling forms between aspects and the base code. Results showed that metrics that take into account fine-grained coupling connections created from aspect-base interactions outperformed the traditional metrics for predicting faults in AO systems.…”
Section: Introductionmentioning
confidence: 99%
“…Software metrics have been widely used in the object-oriented software development in order to improve software maintainability [DANTAS et al 2012]. Recently, some of these metrics were adapted to the context of aspect-oriented programming [CHIDAMBER and KEMERER 1994, HENDERSON-SELLERS 1995, ETZKORN and DELUGACH 2000, SANT'ANNA et al 2003, CECCATO and TONELLA 2004, BURROWS et al 2010 and feature-oriented programming [BARTOLOMEI et al 2006.…”
Section: Implementation-approach-based Metrics and Software Maintenancementioning
confidence: 99%
“…To cite just a few in the context of compositional approaches, Burrows et al proposed a novel metric to specific dependencies in aspect-oriented software systems that were not captured by conventional metrics [BURROWS et al 2010]. In addition, Dantas and colleagues proposed some metrics and conducted an exploratory evaluation about the impact of specific programming techniques on change propagation .…”
Section: Implementation-approach-based Metrics and Software Maintenancementioning
confidence: 99%
See 1 more Smart Citation